A new species of the mesopelagic isopod genus Xenuraega Tattersall, 1909 (Crustacea: Isopoda: Aegidae) from Japan, the second species in the genus - Shimomura, Michitaka; Bruce, Niel L. (Zootaxa, 2019)
Xenuraega bythionekta sp. nov., is described from a single specimen taken off southern Japan. It is the second species of Xenuraega Tattersall, 1909, and extends the known range of the genus from North Atlantic to the northern Pacific Ocean. The species is characterized by the posteriorly narrowed pleotelson, and both uropodal rami being elongate and provided with a mass of long plumose setae. Xenuraega bythionekta sp. nov. is known only from the type locality, Kagoshima Prefecture, southern Japan at a depth of 1178–1179 m.